2018
DOI: 10.1186/s12966-018-0652-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparative validation of self-report measures of sedentary time against an objective measure of postural sitting (activPAL)

Abstract: BackgroundSedentary behaviour is a public health concern that requires surveillance and epidemiological research. For such large scale studies, self-report tools are a pragmatic measurement solution. A large number of self-report tools are currently in use, but few have been validated against an objective measure of sedentary time and there is no comparative information between tools to guide choice or to enable comparison between studies. The aim of this study was to provide a systematic comparison, generalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 23 publications
9
110
0
Order By: Relevance
“…Interestingly, questionnaires that asked participants to recall the proportion of their workday spent sedentary did not significantly differ from inclinometer-assessed sedentary time ranging from an average over-reporting of 9% to under-reporting by 4%. Chastin et al, compared 18 self-report measures of sedentary time against an activPAL and found tools that used a scale to assess the proportion of daily time spent sitting had the lowest amount of missing data and best agreement with deviceassessed measures [25]. Matsuo et al also found that when Japanese workers were asked to indicate the percentage of time spent sitting at work it improved the reliability and validity of the Workers' Sitting and Walking-time Questionnaire (WSWQ) compared to asking them to recall length of time [136].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, questionnaires that asked participants to recall the proportion of their workday spent sedentary did not significantly differ from inclinometer-assessed sedentary time ranging from an average over-reporting of 9% to under-reporting by 4%. Chastin et al, compared 18 self-report measures of sedentary time against an activPAL and found tools that used a scale to assess the proportion of daily time spent sitting had the lowest amount of missing data and best agreement with deviceassessed measures [25]. Matsuo et al also found that when Japanese workers were asked to indicate the percentage of time spent sitting at work it improved the reliability and validity of the Workers' Sitting and Walking-time Questionnaire (WSWQ) compared to asking them to recall length of time [136].…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of two studies were required to conduct a meta-analysis. Several studies [24][25][26][27][28][29][30] included multiple self-report measures compared to one device-assessed outcome (e.g., IPAQ and SBQ compared to activPAL), in this case, the applicable 'arms' were included in the appropriate meta-analysis and the device measure group was split to include half in each comparison as per the Cochrane handbook [23]. If a study reported device-assessed results from both an accelerometer and an inclinometer, the inclinometer data was chosen.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Research has linked SB to a plethora of serious chronic diseases and premature deaths . However, the largest body of evidence is based on imprecise and biased self‐reports possibly underestimating the strength of the relationship . The technological improvements in the past years made it feasible to record SB objectively.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, the largest body of evidence is based on imprecise and biased self-reports possibly underestimating the strength of the relationship. 5,6 The technological improvements in the past years made it feasible to record SB objectively. Nowadays, studies investigating SB use small and lightweight body-worn sensors capable to record free-living behavior over several days.…”
Section: Introductionmentioning
confidence: 99%